Desempenho e morfometria duodenal de frangos de corte submetidos a diferentes níveis de energia e programas de alimentação de 42 a 57 dias de idade - Duarte, Karina Ferreira [UNESP]; Junqueira, Otto Mack [UNESP]; Borges, Liliana Longo [UNESP]; Santos, Elaine Talita [UNESP]; Marques, Rafael Henrique [UNESP]; De Quadros, Thays Cristina Oliveira [UNESP]; Domingues, Carla Heloisa de Faria [UNESP] (FapUNIFESP (SciELO), 2012)
This experiment was conducted to evaluate the use of different energy levels and amino acid recommendations on performance, carcass yield and intestinal morphometry of broilers from 42 to 57 days of age. We used 1,600 one-day old male broilers (Cobb 500) in a completely randomized design arranged in a 2x4 factorial scheme with 3,200 and 3,600 kcal ME/kg and four different feed programs. The metabolizable energy levels and the feed programs did not determine significant differences in carcass characteristics for choosing a level of energy or a feed program, thus the energy level and the recommendations of amino acids that determine the highest cost-benefit ratio should prevail. It was observed that 3,600 kcal ME/kg resulted in some improvement on performance and morphometry of the intestinal mucosa, also the fractioning of digestible amino acid requirements during two periods resulted in worse performance and intestinal villi height.
Performance and duodenum morphometry of broiler chickens submitted to different metabolizable energy levels and feed programs at 42 to 57 days of age
Keywords: Digestible amino acids; Metabolizable energy; Nutritional requirements; Small intestine; Gallus gallus